Kinerja Dinas Lingkungan Hidup Dalam Penanganan Sampah di Kota Merauke - Nugraha Purnama, Erwin; Pardamean Saragih, Dapot; Lewina Lekatompessy, Ransta; Kontu, Fransin (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
Performance is an illustration of the level of achievement of the implementation of a program, activity, or policy in realizing the goals, objectives, mission, and vision of the organization contained in strategic planning in an organization. The purpose of this study was to review the performance of the Merauke Regency Environmental Service in handling waste. The research method used was a qualitative descriptive technique to explain the performance of the Merauke Regency Environmental Service in handling waste. The study's findings indicated that the quality of services carried out by the Environmental Service in Merauke Regency in terms of the performance of community waste transportation in the Merauke city region is considered to have been running well and ideally. However, the responses from both parties, the Environmental Service in Merauke Regency and the people who subscribe to waste transportation, consider that the quality of service still does not meet the standards or has not met the expected expectations. It can be said that the parties in charge have carried out their respective performance or duties in accordance with the duties, principal, and functions.